2020
DOI: 10.1128/jvi.00387-20
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mumps Virus Replication and Transcription by Kinase RPS6KB1

Abstract: Mumps virus (MuV) caused the most viral meningitis before mass immunization. Unfortunately, MuV has reemerged in the United States in the past several years. MuV is a member of the genus Rubulavirus, in the family Paramyxoviridae, and has a nonsegmented negative-strand RNA genome. The viral RNA-dependent RNA polymerase (vRdRp) of MuV consists of the large protein (L) and the phosphoprotein (P), while the nucleocapsid protein (NP) encapsulates the viral RNA genome. These proteins make up the replication and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The intracellular levels of many kinases and phosphatases changed under stress ( STAR Methods ). However, the enzymes responsible for P phosphorylation 65 , 66 need further investigation, with changes in the activity of the enzymes considered alongside their abundance. Second, we observed that the magnitude of increase in replication activity correlated with the severity of stress: genomic RNA level under mild As(III) stress was slightly suppressed until 6 h before showing a dramatic upregulation at 24 h, reminiscent of acute phase infection where transcription is prioritized to generate more material (e.g., polymerase and nucleocapsid protein) required for replication.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular levels of many kinases and phosphatases changed under stress ( STAR Methods ). However, the enzymes responsible for P phosphorylation 65 , 66 need further investigation, with changes in the activity of the enzymes considered alongside their abundance. Second, we observed that the magnitude of increase in replication activity correlated with the severity of stress: genomic RNA level under mild As(III) stress was slightly suppressed until 6 h before showing a dramatic upregulation at 24 h, reminiscent of acute phase infection where transcription is prioritized to generate more material (e.g., polymerase and nucleocapsid protein) required for replication.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins have important roles as transcription and replication machines in MuV. 6 NP protein in MuV plays a role in the formation of the vRNA complex to avoid degradation and initiate the replication process. Inhibition of the NP protein's activity will disturb the initiation of the replication process through an increase of degradation of vRNA in MuV.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins have important roles as transcription and replication machines in MuV. 6 The template that initiates the replication and synthesis of MuV comes from the RNA genome virus (vRNA). Subsequently, vRNA can establish a complex with NP that generates helix-shaped proteins or ribonucleoproteins (RNPs) to avoid degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It also chaperones N to maintain it in an RNA-free form needed for replication [21][22][23][24][25][26][27][28]. In addition, P is an essential actor of viral replication by recruiting a plethora of cellular partners with proviral activities [10,[29][30][31][32][33][34][35][36][37][38][39][40]. The disordered regions of P seem to be of primary importance for these additional functions.…”
Section: Introductionmentioning
confidence: 99%